2008
DOI: 10.1159/000129630
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Expression of High Conductance Ca<sup>2&plus;</sup> Activated K<sup>&plus;</sup> Channels in the Eel Intestinal Epithelium

Abstract: Several types of K+ channels have been identified in epithelial cells. Among them high conductance Ca2+-activated K+ channels (BK channels) are of relevant importance for their involvement in regulatory volume decrease (RVD) response following hypotonic stress. The aim of the present work was to investigate the functional and molecular expression of BK in the eel intestine, which is a useful experimental model for cell volume regulation research. In the present paper using rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 57 publications
(64 reference statements)
3
18
0
Order By: Relevance
“…The involvement of other types of Ca 2+ activated K + channels in RVD was ruled out by the use of clotrimazole and apamine, which were ineffective on the RVD response. BK channels appeared expressed on both membranes by confocal immunofluorescence microscopy as already found in rabbit colonic surface epithelium [54], eel intestine [26], and guinea pig distal colon [55]. Interestingly, they showed a major expression in superficial epithelium with respect to crypts, as previously observed in human colon [56].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The involvement of other types of Ca 2+ activated K + channels in RVD was ruled out by the use of clotrimazole and apamine, which were ineffective on the RVD response. BK channels appeared expressed on both membranes by confocal immunofluorescence microscopy as already found in rabbit colonic surface epithelium [54], eel intestine [26], and guinea pig distal colon [55]. Interestingly, they showed a major expression in superficial epithelium with respect to crypts, as previously observed in human colon [56].…”
Section: Discussionsupporting
confidence: 74%
“…In order to define the precise localization of BK channels in rat distal colonic epithelium, colon explants were fixed in paraformaldehyde diluted to 2% in Hepes-Tris solution from a stock solution of 20% paraformaldehyde in TBS containing (in mM): NaCl 150, Tris 10, MgCl 2 1, EGTA 1 adjusted to pH 7.4 with NaOH, as previously described [26]. Sections of 10 μm thickness were cut along planes perpendicular to the luminal epithelium surface through the use of a microtome (MICROM HM 500) and placed on poly-L-lysine coated glass slides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression studies in oocytes indicated that BK channels were only modestly volume sensitive (305) and that the volume sensitivity seems in many cases to be secondary to an increase in [Ca 2ϩ ] i during cell swelling (107,228). In eel intestinal epithelium, it was recently shown that swelling activation of BK channels was dependent on an increase in [Ca 2ϩ ] i , but that the resulting current was larger than accounted for by the increased [Ca 2ϩ ] i (574), ostensibly due to BK modulation by protein phosphorylation events (107). In some cases, BK channels have been found to be directly stretch-activated (450), which in principle could also account for their swelling activation (see, however, sect.…”
Section: B Swelling-activated K ؉ Channelsmentioning
confidence: 99%
“…VIB). Moreover, pharmacological evidence indicates that apical and basolateral BK channels also play impor-tant roles in the RVD response of the eel intestinal epithelium (574). In the killifish opercular epithelium, osmotic control of Cl Ϫ secretion across the operculum epithelium was proposed, albeit based on colocalization and pharmacological evidence only, to involve the following events: 1) hyperosmotic activation of NKCC1 on the basolateral membrane via PKC, MLCK (362), p38 MAPK, OSR1, and SPAK (624); 2) deactivation of NKCC by hypotonic cell swelling and a protein phosphatase (624); and 3) a protein tyrosine kinase acting on FAK, which seems to have an important, not yet defined function in regulating NKCC activity (624).…”
Section: Osmotic Regulation Of Salt Transportmentioning
confidence: 99%